The community structure of a mangrove stand in Bargy. Trapiche, Oton, Iloilo. - Morillo, Laureen Bornillo (2003.)
The community structure of a mangrove stand in Brgy. Trapiche, Oton was studied. Transect line plot method was applied for the seedlings and total count of individuals was used for the trees and saplings. The eight true mangrove species found were Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, Bruguiera cylindrical, Sonneratia alba, Avicennia marina, Lumnitzera racemosa and Xylocarpus mekongensis. The stand basal area was found to be 3.97 m2/ha. Avicennia marina seedlingd had the highest importance value of 220.7. The species diversity value for the seedlings is only 0.4071 due to the uneven distribution of the mangrove species. The community structure was assessed in relation to the physico-chemical parameters, which include tidal depth, salinity, soil texture and pH, organic matter, phosphorus and potassium content.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Mangrove -- Trapiche, Oton, Iloilo